The perspective of preschool teachers on the use of digital technology - Bay, Dondu Neslihan (Southeast Asia Early Childhood Journal, 2022)
Rapidly developing digital technology has also entered educational settings. Teachers play a crucial role in using digital technology in education. This study aims to examine preschool teachers’ views on using digital technology in early childhood learning settings in Turkey (N=43). Data were obtained qualitatively through closed and open-ended interview questions from teachers working in 16 different provinces of Turkey. Data were collected online with a semi-structured interview form. In the study, teachers’ views on using digital technology in their homes and classrooms and the role of digital technology in preschool education were evaluated. The data obtained through the interview were analyzed by inductive analysis. As a result of the study, it was found that teachers possessed web-based technologies, and they mostly used smartphone applications (97.7%). On the other hand, they used digital technology less in their classrooms (48.8%); teachers generally used digital technology with their devices, such as smartphones. The findings on the use of digital technology in preschool education revealed that teachers grouped digital technology applications under four themes, teacher, education, program, and family involvement. Regarding teachers’ views, the pros of digital technology are: it makes it easier to do their job (46.5%), facilitates learning in education (39.5%), facilitates the transfer of gains (41.9%), and facilitates communication with family (34.9%). On the other hand, teachers’ views revealed some negativities regarding digital technology. In the 21st century, where digital technology has become an indispensable element, it is considered necessary to provide children with the skills to use digital technology. Therefore the positive aspects of digital technology in education declared in teachers’ statements are an important result of the research.